Brane tilings and non-commutative geometry - Eager, Richard (Journal of high energy physics, 2011)
We derive the quiver gauge theory on the world-volume of D3-branes transverse to an L a,b,c singularity by computing the endomorphism algebra of a tilting object first constructed by Van den Bergh. The quiver gauge theory can be concisely specified byan embedding of a graph into a face-centered cubic lattice. In this description, planar Seiberg dualities of the gauge theory act by changing the graph embedding. We use this description of Seiberg duality to show these quiver gauge theories possess periodic Seiberg dualities whose existence were expected from the AdS/CFT correspondence.